2011
DOI: 10.4314/ajpsy.v14i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of common phobias and their socio-demographic correlates in children and adolescents in a traditional developing society

Abstract: Objective: The aim of this study was to identify the most common phobias in children and adolescents and to determine the prevalence, age distribution, and socio-demographic correlates of phobias. Method: This was a prospective cross-sectional study conducted at public and private schools from July 2009 to February 2009. The questionnaire included socio-demographic information, extra-curricular activities and hobbies, behaviour at home and various phobic fears and it was distributed among children aged 6 to 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 13 publications
(15 reference statements)
4
19
1
Order By: Relevance
“…In a study conducted by Bener et al to see prevalence of common phobias in children and adolescents, it was found that phobias were more prevalent in female students (21.9%) than in males (16.8%), with a female to male sex ratio of 1.3:1. 4 SAD was found more in students belonging to age group >21 years (21.87%) but it was not statistically significant. These results are similar to study conducted by Upadhyay, we found that there was no statistically significant difference in social anxiety levels with respect to age and residential status.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In a study conducted by Bener et al to see prevalence of common phobias in children and adolescents, it was found that phobias were more prevalent in female students (21.9%) than in males (16.8%), with a female to male sex ratio of 1.3:1. 4 SAD was found more in students belonging to age group >21 years (21.87%) but it was not statistically significant. These results are similar to study conducted by Upadhyay, we found that there was no statistically significant difference in social anxiety levels with respect to age and residential status.…”
Section: Discussionmentioning
confidence: 72%
“…In a study about phobias, conducted by Bener et al shows that phobias are less common among children and adolescents if education of their mother or father is higher but no significant association was found. 4 SAD was found statistically more in students, after age of 18 years, lived at hostel or lived alone (22.05%). This finding is sane as found in a study conducted by Shah et al about social phobia among Indian university students, shown that higher SPIN scores found in students residing in hostel.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…SAD is synonymous to social phobia and is the most common anxiety disorder (Bener, Ghuloum, & Dafeeah, 2011). The 12-month prevalence rate of SAD in the United States is approximately 7% (Kessler et al, 2005;Kessler, Petukhova, Sampson, Zaslavsky, & Wittchen, 2012;Ruscio et al, 2008).…”
Section: Psychological Disordersmentioning
confidence: 99%
“…Studies published in recent years confirm the high prevalence of specific phobias in the general population, especially in children (Bener, 2011).…”
Section: Along With Generalized Anxiety Disorder (Gad) and Separationmentioning
confidence: 64%